Von Hippel-Lindau syndrome: a rare case report from a tertiary care hospital - Avva, Veena Santoshi; Reddy, D. Nageshwar (International Journal of Advances in Medicine, 2025)
Von Hippel-Lindau (VHL) is a diagnostic challenge due to the fact that it is rare and as stated above, presentation is also not typical in all cases. It is quite rare as prevalence ranges from 1 per every 30,000-50,000 population per year. Present case is unique in the sense of difficulty in the diagnosis at previous clinics. She had retinal angioma, left renal mass, infertility. Thus, multiple presentations make the diagnosis difficulty and thereby treatment. Hence, it is necessary to present all possible cases which come across during the routine clinical care so that the physicians and surgeons bear this differential in mind.